Status of Work and Family Support of Mothers Causes Low Visit to Posyandu - Putu Dian Prima Kusuma Dewi; Lina Anggaraeni Dwijayanti; Putu Sukma Megaputri (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2018)
Growth monitoring is one form of power-based health activities are managed and organized society of, by, for and with the community in the implementation of health development. Efforts development of quality human resources to optimize the potential development of the child can be carried evenly when posyandu done effectively and efficiently. But in its development posyandu not been utilized optimally. The purpose of this study was to identify the causes of poor mothers visit to Posyandu. The research was conducted in the village of Bulian because Posyandu visit the village to its lowest Bulian 48.68%. This study is a cross-sectional analytic study using logistic regression analysis. This document is a live template file. The various components of your paper [title, text, heads, etc.] are exactly defined on the style sheet, as illustrated by the portions given in this document. Do not include any special characters, symbols, or math in your title or abstract. The authors must follow the guidelines given in the document for the papers to be published. You can use this document file as both an instruction set and as a template into the which you can type your own text.